2020
DOI: 10.21608/jpp.2021.57940.1014
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Harvest Treatments On Canino Apricot Trees to Improve Yield, Fruit Quality at Harvest and During Storage

Abstract: The present study was conducted on eighteen years old Canino apricot trees grown in a private orchard at Motobus, Kafr El-Sheikh governorate, Egypt in 2019 and 2020 seasons to evaluate the effects of preharvest foliar treatments of potassium sulphate at 1.5% and calcium chloride at 2% individually or in combination in addition to Control (tap water) on yield, fruit quality at picking date and during cold storage at 0±1°C with 90-95 % RH. Canino apricot trees were sprayed three times starting after full bloom, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Therefore, it can be concluded that there is a positive correlation between calcium application and fruit firmness, and this increase was much pronounced in treatment of calcium citrate 1.5% as compared with the other treatments. These findings are supported by Mahitha et al (2018) and Ennab et al (2020).…”
Section: Fruit Firmness (Newton)supporting
confidence: 79%
See 1 more Smart Citation
“…Therefore, it can be concluded that there is a positive correlation between calcium application and fruit firmness, and this increase was much pronounced in treatment of calcium citrate 1.5% as compared with the other treatments. These findings are supported by Mahitha et al (2018) and Ennab et al (2020).…”
Section: Fruit Firmness (Newton)supporting
confidence: 79%
“…Also, El-Dengawy et al, (2019) cleared that calcium chloride at 2% reduced total soluble solids/acid ratio of peach under storage. In this line, Ennab et al, (2020) revealed that application of 2 % CaCl2 showed the lowest SSC/acid ratio of apricot under cold storage. The SSC/acid ratio is the most important parameter in evaluating fruit quality, it determines fruit flavor harmony and consumer acceptability (Abrol et al, 2017).…”
Section: Ssc/acid Ratiomentioning
confidence: 76%